PERANAN SIDIK JARI DALAM PROSES PENYIDIKAN UNTUK MENENTUKAN PELAKU TINDAK PIDANA - Anny Yuserlina (JCH (Jurnal Cendekia Hukum), 2017)
Taking the latent fingerprints is present on the objects at the scene of the case, after which the object is held or tramped can be done in two ways, namely through puder and chemical process. Besides, fingerprint can also be done at the Investigation Office against suspects and people who want to take care of the letters, such as SKKB. In this case fingerprint is performed on a rolled impression and plain impression columns and columns for information along with the identity of the person whose fingerprints are taken. In the case of the perpetrator or suspect of a crime not yet caught, the fingerprint is one of the objective physical proofs in recognizing the return and identification of its behavior by comparing fingerprints between suspected persons or fingerprints that have been stored in police files with latent fingerprints found from crime scenes (TKP). it uses the empirical yuidist method which is empirical juridical itself according to Fred N Kerlner: as the questions tried to find the answer. It can be concluded that the authors want to approach the role of fingerprints in the investigation process tub from juridical aspect (legislation) maupundalam aspect p the implementation of the community (police). So in conclusion the latent fingerprint is found on the objects at the scene of the case, after the object is held or tramped can be done in two ways, namely through puder and chemical process. Besides, fingerprint can also be done at the Investigation Office against suspects and people who want to take care of the letters, such as SKKB. In this case fingerprint is performed on a rolled impression and a plain impression and a column for information along with the identity of the person fingerprints are taken.